The Development of Competition and Raising Efficiency in Electric Engineering Complex - L. N. Orlova; D. A. Vasilyev (Вестник Российского экономического университета имени Г. В. Плеханова, 2020)
The high degree of monopolization of the power complex in the Russian Federation, on the one hand, and state regulation, on the other hand, can cause a decline in the efficiency of entrepreneurial structures’ functioning in electric engineering. From the point of view of theory and methodology the research studies possibilities to shape competitive relations in electric engineering and analyzes regular risks in electric engineering companies’ work. In practical view the lines in raising the efficiency of entrepreneurial structures are investigated. The authors show feasibility of using DEA methods and the standard method for raising the efficiency of electric engineering companies’ work and fixing a grounded tariff on electric power. As a scientific tool for conducting the research the authors chose such general academic and specific methods as the method of system analysis, the method of retrospective analysis, analytical methods of data research. Empiric materials of the research are presented by information of the Federal Service of State Statistics, public data of monitoring the adopted tariff solutions provided by the Federal Antitrust Service.